Isotherm and Thermodynamics Study of Congo Red and Procion Red Adsorption over Natural and Zn/Fe Pillared Bentonite - Desnelli Desnelli; Heni Yohandini; Elisa Nurnawaty; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The effect of initial Congo Red and Procion Red concentration on isotherm adsorption and thermodynamic adsorption study using natural and Zn/Fe Pillared bentonite have been conducted. The adsorbents were also characterized by Fourier transform infrared (FTIR), X-Ray Diffraction (XRD), and Scanning electron microscope-energy dispersive X-Ray analysis (SEM-EDX). The study showed that the optimum dye removal of Congo Red and Procion Red was obtained at the initial dye concentration of 80 mg/L. The adsorption isotherm study showed that the Congo Red and Procion Red adsorption on natural and Zn/Fe Pillared bentonite followed the Freundlich isotherm model. The adsorption thermodynamics study showed that the adsorption of Congo Red and Procion Red occurred endothermically, wheraas the positive value of entropy indicated a high level of disorder of adsorption for both dyes. Furthermore, the FTIR, XRD, and SEM-EDX analysis showed that the pillarization of Zn/Fe on bentonite successfully well occurred, and it could be concluded that the adsorption of Congo Red using natural and Zn/Fe pillared bentonite showed a better adsorption process than Procion Red.